Establishment of Universal Primary Education System in the Democratic Republic of Georgia (1918-1921) - Iremadze, Irakli («Մռավ» հրատ․)
The access to education as a fundamental human right and a cornerstone of social and political rights represents one of the most significant achievements for the contemporary world. However, until 1917 citizens of Georgia and the broader Caucasus region were denied access to these fundamental rights. 1918թ. մայիսին Վրաստանի անկախության հռչակումից հետո քայլեր ձեռնարկվեցին հանրապետությունում համընդհանուր կրթական համակարգի ստեղծման ուղղությամբ: Բարեփոխումներն ընթանում էին բարդ ռազմաքաղաքական և տնտեսական խոր ճգնաժամի պայմաններում: Հոդվածում ներկայացվում է բարեփոխումների ընթացքը և ծագող խնդիրները:
Keywords: History